2015
DOI: 10.1021/acs.jpcb.5b08985
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Degradation of the Monolayer of 1-Palmitoyl-2-Oleoyl-sn-Glycero-3-Phosphocholine (POPC) in Low-Level Ozone

Abstract: Ambient ozone is a common pollutant in the atmosphere that has an extremely high oxidative ability, can dramatically change the structure and functionality of biomolecules, and is harmful to public health. However, the knowledge about the influence of low-level ozone is still very limited at a molecular level. In the present study, the monolayer of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC, 16:0-18:1 PC) as well as its binary mixed monolayer with 1,2-dipalmitoyl-sn-glycero-3-phosphatidylcholine (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 54 publications
0
40
0
Order By: Relevance
“…Correspondingly, the spectral weight of the Ni L 2 -edge at ~873 eV increases upon charge and decreases upon discharge. This overall lineshape evolution of both the L 3 - and L 2 -edges is a typical sXAS evidence of Ni 2+ in the bulk of LNF15 particles oxidized to Ni 3+ and Ni 4+ upon charge, and reduced back to Ni 2+ on discharge 30, 31 . Overall, changes in the Ni L-edges are small compared with other Ni systems 31 , and the Ni 2+ signal remains strong even after charging to 4.6 V, suggesting that only a small portion of the Ni redox reservoir is utilized in LNF15 during cycling.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…Correspondingly, the spectral weight of the Ni L 2 -edge at ~873 eV increases upon charge and decreases upon discharge. This overall lineshape evolution of both the L 3 - and L 2 -edges is a typical sXAS evidence of Ni 2+ in the bulk of LNF15 particles oxidized to Ni 3+ and Ni 4+ upon charge, and reduced back to Ni 2+ on discharge 30, 31 . Overall, changes in the Ni L-edges are small compared with other Ni systems 31 , and the Ni 2+ signal remains strong even after charging to 4.6 V, suggesting that only a small portion of the Ni redox reservoir is utilized in LNF15 during cycling.…”
Section: Resultsmentioning
confidence: 59%
“…This overall lineshape evolution of both the L 3 - and L 2 -edges is a typical sXAS evidence of Ni 2+ in the bulk of LNF15 particles oxidized to Ni 3+ and Ni 4+ upon charge, and reduced back to Ni 2+ on discharge 30, 31 . Overall, changes in the Ni L-edges are small compared with other Ni systems 31 , and the Ni 2+ signal remains strong even after charging to 4.6 V, suggesting that only a small portion of the Ni redox reservoir is utilized in LNF15 during cycling. Additionally, because the main sXAS feature of Ni 4+ sits at higher energy compared with that of Ni 2+ and Ni 3+ 31 , the weak spectral weight above 855 eV indicates that most Ni has not been oxidized to Ni 4+ in LNF15.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Several studies by Finlayson-Pitts and co-workers have shown that unsaturated phospholipids are readily oxidized by O 3 from the “top down” to generate secondary ozonides and a number of products. 122124 The group of Ye 125,126 probed the structure and stability of phospholipids in low ozone concentration by a combination of π–A isotherms, vibrational spectroscopy, and force microscopy. Their results demonstrate that the CC moieties in the unsaturated lipids are selectively oxidized by a trace amount of ozone in the ambient environment.…”
Section: Bioaerosol Reactivity – Oxidant Chemistry and Other Reactionmentioning
confidence: 99%